Insect Venom Immunotherapy: Analysis of the Safety and Tolerance of 3 Buildup Protocols Frequently Used in Spain - Gutiérrez Fernández, D; Moreno-Ancillo, A; Fernández Meléndez, S; Domínguez-Noche, C; Gálvez Ruiz, Pablo; Alfaya Arias, T (Journal of Investigational Allergology and Clinical Immunology, 2017)
Introduction: Hymenoptera venom immunotherapy (VIT) is an effective treatment but not one devoid of risk, as both local and systemic adverse reactions may occur, especially in the initial phases. We compared the tolerance to 3 VIT buildup protocols and analyzed risk factors associated with adverse reactions during this phase. Materials and Methods: We enrolled 165 patients divided into 3 groups based on the buildup protocol used (3, 4, and 9 weeks). The severity of systemic reactions was evaluated according to the World Allergy Organization model. Results were analyzed using exploratory descriptive statistics, and variables were compared using analysis of variance. Results: Adverse reactions were recorded in 53 patients (32%) (43 local and 10 systemic). Local reactions were immediate in 27 patients (63%) and delayed in 16 (37%). The severity of the local reaction was slight/moderate in 15 patients and severe in 13. Systemic reactions were grade 1-2. No significant association was found between the treatment modality and the onset of local or systemic adverse reactions or the type of local reaction. We only found a statistically significant association between severity of the local reaction and female gender. As for the risk factors associated with systemic reactions during the buildup phase, we found no significant differences in values depending on the protocol used or the insect responsible. Conclusions: The buildup protocols compared proved to be safe and did not differ significantly from one another. In the population studied, patients undergoing the 9-week schedule presented no systemic reactions. Therefore, this protocol can be considered the safest approach.
Keywords: allergy; immunotherapy; insect venom immunotherapy; buildup protocols; systemic reaction; local reaction; hymenoptera; apis mellifera; vespula species; polistes species; JCR; Scopus